Synthesis and characterization of waste newspaper cellulose based flocculant for water treatment - Yusoff, Nor Aida (2016)
The quaternized cellulose derivatives (QCs) were synthesized through etherification reaction of cellulose extracted from waste newspaper (WNP) for water treatment. The cellulose was extracted from WNP by chemical treatment. The characterization results by using Fourier transform infrared (FTIR) spectrophotometer, x-ray diffractometer, thermogravimetric analysis, and scanning electron microscope show that the WNP properties changed after chemical treatment and the extracted product was confirmed cellulose. The QCs were homogeneously synthesized by reacting extracted cellulose with 3-chloro-2-hydroxypropyl trimethylammonium chloride (CHPTAC) using sodium hydroxide/urea aqueous solution as a reaction medium. The structure and properties of QCs were characterized using FTIR spectrophotometer, carbon nuclear magnetic resonance, hydrogen nuclear magnetic resonance, gel permeation chromatography and elemental analysis. The results indicated that the QCs having various nitrogen content could be obtained by changing the molar ratio of cellulose unit to CHPTAC. The flocculation performance of the QCs was evaluated by using a synthetic kaolin suspension carried out using the standard jar test method at different coagulant/flocculant dosages, kaolin concentrations, pH values, and settling times. It was found that the QC-15 exhibited a highly effective flocculation capability as compared to other synthesized QCs for over a wide pH values. The rate constant (k) of the coagulation/flocculation kinetics increased with cationic content. The sludge specific resistance decreased with increasing coagulant/flocculant dosage. The coagulation/flocculation of the surface water shows that the QC-15 was effective for the removal of turbidity and total suspended solid as compared to biochemical oxygen demand, chemical oxygen demand and pH. These results demonstrated that the WNP cellulose can be used for the development of effective and eco-friendly coagulant/flocculants which have good potential applications in water treatment.